2020
DOI: 10.1155/2020/6571484
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Chlorogenic Acid on Mitochondrial Dysfunction-Mediated Apoptotic Death of DA Neurons in a Parkinsonian Mouse Model

Abstract: Mitochondrial dysfunction and oxidative stress characterize major factors involved in the activation of complex processes corresponding to apoptosis-mediated neuronal senescence of dopaminergic neurons (DA) in Parkinson’s disease (PD). Here, we evaluated the molecular mechanisms participating in the treatment of a 1-methyl-4-phenyl-1,2,3,6-tetrahydopyridine- (MPTP-) intoxicated PD mouse model in response to chlorogenic acid (CGA). The results indicate that CGA treatment significantly improved the motor coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 85 publications
3
79
0
1
Order By: Relevance
“…CGA reduced the drug-induced neuroinflammation in substantia nigra by regulating the NF-κB expression and release of certain pro-inflammatory mediators such as TNF-α and interleukin (IL)-1β with the enhanced expression of anti-inflammatory cytokine IL-10. The similar experiments also demonstrated that CGA inhibited the activation of proapoptotic proteins including B-cell lymphoma-2 (Bcl-2) associated X protein (Bax) and caspase-3 and elevated the expression of antiapoptotic protein like Bcl-2 to prevent apoptosis [ 127 ]. CGA improved phosphorylation state of Akt, ERK1/2, and GSK-3 β which was downregulated as an effect of the drug-induced toxicity.…”
Section: Parkinson’s Disease (Pd)mentioning
confidence: 99%
“…CGA reduced the drug-induced neuroinflammation in substantia nigra by regulating the NF-κB expression and release of certain pro-inflammatory mediators such as TNF-α and interleukin (IL)-1β with the enhanced expression of anti-inflammatory cytokine IL-10. The similar experiments also demonstrated that CGA inhibited the activation of proapoptotic proteins including B-cell lymphoma-2 (Bcl-2) associated X protein (Bax) and caspase-3 and elevated the expression of antiapoptotic protein like Bcl-2 to prevent apoptosis [ 127 ]. CGA improved phosphorylation state of Akt, ERK1/2, and GSK-3 β which was downregulated as an effect of the drug-induced toxicity.…”
Section: Parkinson’s Disease (Pd)mentioning
confidence: 99%
“…Daveri et al also reported that cyanidin and delphinidin modulated the inflammation process through the attenuation of PTP1B and downregulation of NF- κ B [ 62 ]. Many studies also discussed the attenuation of inflammation may benefit PD progression in in vitro and in vivo models [ 63 67 ]. Moreover, Xu et al demonstrated that punicalagin could promote M2 polarization of the macrophage by PTP1B blocking [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…In rotenone-injected mice, chlorogenic acid ameliorated degeneration of dopaminergic neurons in the substantia nigra and upregulated the antioxidative molecules–metallothionein-1 and 2, in striatal astrocytes [ 321 ]. In the study by Singh et al [ 322 ], chlorogenic acid improved motor coordination and neurobehavioral activity in the MPTP-induced model of Parkinson’s disease in mice. Of note, the behavioral effects were accompanied by reduced degeneration of dopaminergic neurons in the substantia nigra.…”
Section: Neuroprotective Effects Of Coffee Bioactive Compoundsmentioning
confidence: 99%
“…Moreover, chlorogenic acid improved mitochondrial function, suppressed ROS generation, increased SOD and mitochondrial GSH activity, inhibited activation of proapoptotic proteins (Bax and caspase-3), and elevated expression of the anti-apoptotic protein (Bcl2). Since it improved the phosphorylation state of Akt, ERK1/2, and GSK3β, it appears that the neuroprotective effects of chlorogenic acid against MPTP-induced neurotoxicity are mediated, at least in part, by the GSK3β phosphorylation-associated Akt/ERK pathway [ 322 ]. It is also worth noticing that chlorogenic acid attenuated the extensive release of release of TNF-α and IL-1β in the substantia nigra of the LPS-injected mice suggesting that this compound may suppress inflammatory response or damage in neurodegenerative diseases including Parkinson’s disease [ 323 ].…”
Section: Neuroprotective Effects Of Coffee Bioactive Compoundsmentioning
confidence: 99%